Generations learning together: pilot study for a multigenerational program. Issue 3 (3rd July 2018) - Bertram, Anita Glee; Burr, Brandon K.; Sears, Kaye; Powers, Melissa; Atkins, LaDonna; Holmes, Tawni; Kambour, Tina; Kuns, J. Brooke
ABSTRACT: Generations need to spend time in meaningful activities to facilitate more healthy interactions. An interdisciplinary team worked together to implement an enriching, intergenerational project with 4 year olds, college students, and older adults. College students played an active role in planning/facilitating activities. The overall objective of the research was assessing perceptional change between the generations using pre/posttests with college students, pre-post interviews with older adults, and pre-post teacher led discussions with children. Findings suggest that older adults and college students had improved perceptions. Children's perceptions remained negative with some positive perceptions.